1997
DOI: 10.1002/(sici)1096-9896(199701)181:1<31::aid-path722>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of Human Monocytes/Macrophages Inmycobacterium Tuberculosis Infection

Abstract: Tuberculosis (TB) is still a major health problem, both as a single disease entity and as a cofactor in AIDS. The interaction between macrophage and Mycobacterium tuberculosis (MTB) is a critical step in the establishment of an early chronic infection. This study analyses the capacity of MTB to induce apoptosis in cells obtained by broncho‐alveolar lavage (BAL) from patients with reactive pulmonary tuberculosis and from AIDS patients with disseminated pulmonary tuberculosis. Apoptosis was increased three‐fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(98 citation statements)
references
References 23 publications
7
89
2
Order By: Relevance
“…The induction of downregulatory cytokines, such as IL-10 and transforming growth factor-b, can inhibit interferon (IFN)-c production by T cells and block or inhibit macrophage activation and apoptosis (Flesch et al, 1994;Othieno et al, 1999). It is widely known that in alveolar macrophages, apoptosis is a common defence mechanism against M. tuberculosis infection via a TNF-a-mediated pathway (Placido et al, 1997). Monocytes from patients with active TB when compared to those from healthy donors are not only likely to secrete more IL-10 than TNF-a in response to stimulation with PPD, but they are also more likely to undergo necrosis than apoptosis (Gil et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The induction of downregulatory cytokines, such as IL-10 and transforming growth factor-b, can inhibit interferon (IFN)-c production by T cells and block or inhibit macrophage activation and apoptosis (Flesch et al, 1994;Othieno et al, 1999). It is widely known that in alveolar macrophages, apoptosis is a common defence mechanism against M. tuberculosis infection via a TNF-a-mediated pathway (Placido et al, 1997). Monocytes from patients with active TB when compared to those from healthy donors are not only likely to secrete more IL-10 than TNF-a in response to stimulation with PPD, but they are also more likely to undergo necrosis than apoptosis (Gil et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines are known to play a significant role in the pro-and antiinflammatory components respectively of the immune response to M. tuberculosis infection (Flynn et al, 1995;Gong et al, 1996). Mycobacterial proteins/lipids released from the phagosome of M. tuberculosis-infected macrophages have also been shown to modulate levels of cytokine secretion during infection, to the advantage of the pathogen (Gil et al, 2004;Placido et al, 1997;Rivera-Marrero et al, 2004).…”
Section: Cytokine Release By Human Monocytes In Response To Stimulatimentioning
confidence: 99%
“…These data indicate that M. tuberculosis challenge in some way sensitizes AMF to autocrine and/or paracrine TNFa-mediated apoptosis. Apoptosis of primary human monocyte-derived macrophages (MDMF) following exposure of M. tuberculosis H37Rv in vitro was reported by Placido et al, 23 and Klingler et al 24 noted a similar response to H37Ra. The data of Placido and Keane both indicate that apoptosis requires challenge with live mycobacteria; heat-killed organisms had no effect on macrophage viability.…”
Section: Macrophage Apoptosis In Response To M Tuberculosis Infectiomentioning
confidence: 99%
“…Apoptosis of immune cells including macrophages has been found to occur in inflammatory diseases [1][2][3][4][5]. Apoptosis of activated macrophages may serve to restrict and focus the immune response, but it may also reduce the host defenses against infectious pathogens or contribute to immune suppression.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the lifespan of macrophages in inflammation sites was extended by survival factors such as apoptosis inhibitor and nerve growth factor secreted by macrophages or other cells [9,10]. On the other hand, macrophage death has been observed in many inflammatory diseases [1][2][3][4][5]. Macrophage death could result from different causes.…”
Section: Introductionmentioning
confidence: 99%